Laissez faire technique after xanthelasma palpebrarum excision: a case report - Jose Miguel Ambat; Kunihiro Musashi; Naoyuki Morishige; Osama AlSheikh; Hirohiko Kakizaki (Journal of Cosmetic Medicine)
Xanthelasma palpebrarum is a condition caused by lipid deposition into the dermis. Typical lesions present as yellowish plaques, or papules, commonly affecting the medial aspect of the upper eyelids. Management of xanthelasma palpebrarum generally includes medical, laser, and surgical therapies. These treatment modalities cause good outcomes but also show complications, including ectropion, skin discoloration, and eyelid margin deformities. The authors presented the case of 76-year-old female with xanthelasma palpebrarum on both upper and lower eyelids, treated with simple full-thickness surgical excision with laissez-faire technique. The laissez-faire technique is a treatment comprised of healing with secondary intention without other treatment modalities. Healing via the laissez-faire technique was utilized for wound closure. Post-operative cosmesis, eyelid function, and contour were satisfactory up to 3 months post-operatively. The laissez-faire technique is an acceptable treatment for surgical site closure post-excision of xanthelasma palperarum, especially with multiple lesions. This method results in good cosmesis, retention of eyelid function, and avoids sequelae of common treatment modalities.